2017
DOI: 10.1073/pnas.1708070114
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved measurements of an ion channel conformational change driven by a membrane phase transition

Abstract: Using temperature-jump infrared spectroscopy, we are able to trigger a gel-to-fluid phase transition in lipid vesicles and monitor in real time how a membrane protein responds to structural changes in the membrane. The melting of lipid domains in 1,2-dimyristoyl-sn-glycero-3-phosphocholine vesicles is observed to occur in as fast as 50 ns, with a temperature dependence characteristic of critical slowing. Gramicidin D (gD) added to the membrane responds primarily to the change in thickness of the membrane on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…It has been reported earlier that the increase in non-hydrogen bonded carbonyl frequency is responsible for the flexibility as well as mobility and this effect can cause bilayer thinning. 14…”
Section: Kmp-11 Binding Changes the Properties Of Lipid Molecules Andmentioning
confidence: 99%
“…It has been reported earlier that the increase in non-hydrogen bonded carbonyl frequency is responsible for the flexibility as well as mobility and this effect can cause bilayer thinning. 14…”
Section: Kmp-11 Binding Changes the Properties Of Lipid Molecules Andmentioning
confidence: 99%
“…Kota et al [9] determined the orientation of gA in different lipid vesicles using polarized attenuated total reflection infrared spectroscopy and reported that the orientation of the gA molecules depends on the lipid polar head groups and surface hydration. Time-resolved IR spectroscopy was employed by Stevenson et al to study the effect of the lipid phase transition on the conformation of gramicidin within the lipid bilayer [10]. Naik and Krimm applied the normal mode analysis to calculate IR spectra of different gA conformations and demonstrated that the position of the amide I band can be used to identify different conformations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Conversion between conformers has been studied in lipid environments [ 21 , 22 , 23 , 24 , 25 ]. In membrane lipid environments, the rate of conversion from the double-stranded helical dimer into the channel dimer is dependent on environmental factors, such as temperature and ionic strength [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%